Intensification of thermo-hydraulic and exergetic performance by wire matrix and wavy tape: An experimental study. (February 2021) - Varun, K.; Arunachala, U.C.
Abstract: The present study contemplates diverse flow range (1500 <  Re  < 15, 000) to deduce the thermo-hydraulic and exergy performance of the twisted tape, wire matrix and wavy tape inserts (with three variants each) involving water as the heat transfer fluid in the 26.5 mm diameter tube. The testing of all the inserts under an identical operating condition (heat flux of 6 kW/m 2 ) ensured realistic energy parameters viz. wall temperature, heat transfer coefficient, exergy destruction and second law efficiency. In comparison, wavy tape proved to be the most cost-effective and lucid design insert which can be incorporated in compact heat exchangers as the thermal advantage is highest as indicated by the performance evaluation criterion – I. Even the lowest exergy destruction complemented by highest second law efficiency made it perfect for the waste heat recovery process. Further, wire matrix being the convoluted design, gave maximum thermo-hydraulic rating (performance evaluation criterion – III) to suggest it in the tubular heat exchangers. Hence based on the thermal or thermo-hydraulic accountability, widely used twisted tape can be replaced by wavy tape or wire matrix. To explore its application further, Nu and f correlations have also been developed and validated. Graphical abstract: Unlabelled Image Highlights: Thermo-hydraulic performance of wire matrix and wavy tape is analyzed. Influence of flow regime on insert characteristics have been discussed. Based on energy parameters, types of insert are recommended for different thermal systems.